Weed Diversity and Uses: a Case Study from Tea Plantations in Northern Thailand - Kamonnate Srithi (2018)
© 2017, The New York Botanical Garden. Based on concerns that useful weed diversity in agroecosystems as well as associated traditional knowledge may be declining due to agricultural intensification and indiscriminate eradication of weeds, we studied weed diversity and use by local ethnic groups in tea plantations in northern Thailand under different agricultural intensities and landscape complexities, namely agroforestry, organic, and Good Agricultural Practice (GAP) based conventional system. In each system, we sampled five tea plantations using belt-transects of 25 m2. Use data were collected through interviews with specialist informants. We recorded 214 weed species (gamma-diversity) of which 66 were useful. Agroforestry system had the highest alpha- and beta-weed diversity, suggesting that the low agricultural intensity and high landscape complexity in this system is associated with higher weed diversity in tea plantations. The common weed species were clearly different in the three systems and only a small fraction (22 species) of widespread weeds was shared among them, resulting in low weed similarity between systems. The 66 useful species of weeds were mostly for food and medicine. Uses of some weeds were shared between systems. Many of the useful weeds are invasive species, suggesting that they are prevalent and inexpensive plant resources for rural people and could represent alternative resources in the future. Because the occurrence of invasive weeds may affect the natural habitats of the native flora, integrating the exploitation of weeds into weed management strategies may reduce the weed population while sustaining agrobiodiversity and conserving associated traditional knowledge in the long term.